Analisis Penerapan Motivasi Kerja Terhadap Prestasi Kerja Perangkat Desa Di Desa Bongo IV Kecamatan Paguyaman Kabupaten Boalemo (Ditinjau Dalam Ekonomi islam) - Mardiana, Andi; Latif, Abdul; Olii, Zein (Scimadly Publishing, 2022)
This study aims to determine the Analysis of the Application of Islamic Work Motivation to the Work Performance of Village Officials in Bongo IV Village, Paguyaman District, Boalemo Regency, while the research method used is a qualitative descriptive method using data collection techniques used in this study are observation interviews and documentation. The data analysis technique used is descriptive qualitative, namely collecting data, then compiling, explaining and analyzing it. The results of the research conducted by the author can be concluded that the application of Islamic work motivation in the Bongo IV Village office is in accordance with the needs of the Village Officials and has resulted in the achievements that have been achieved by the Village Officials. Although non-Muslim Bergama leaders for the application of Islamic work motivation are further enhanced so that village officials who are Muslim can improve work performance even better.